2009
DOI: 10.1016/j.geomorph.2008.03.014
|View full text |Cite
|
Sign up to set email alerts
|

Geomorphic mapping in endorheic catchments in the Spanish Pyrenees: An integrated GIS analysis of karstic features

Abstract: A B S T R A C TDigital elevation models (DEMs) can be a useful tool to assess morphologically and hydrologically active processes. This paper presents a method to obtain accurate DEMs, an analysis of DEM errors and the benefits of GIS techniques for mapping geomorphological features and active processes in the karstic endorheic catchment with three permanent lakes (Estaña lakes) in the External Ranges of the Spanish Pyrenees. Field work revealed the lack of accuracy in the original DEM. A method was then propo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0
3

Year Published

2009
2009
2014
2014

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(24 citation statements)
references
References 20 publications
1
20
0
3
Order By: Relevance
“…with a mean slope of 17 per cent and steep slopes (> 22Á5 per cent) occupy 26 per cent of the total surface. The geomorphic units of the study area were identified by López-Vicente et al (2009) and include two collapse dolines that are associated to the lake, one uvala, nine gullies with a maxima length of 323 m and a main stream that measures 1421 m, together with the presence of colluvial, alluvial and doline deposits (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…with a mean slope of 17 per cent and steep slopes (> 22Á5 per cent) occupy 26 per cent of the total surface. The geomorphic units of the study area were identified by López-Vicente et al (2009) and include two collapse dolines that are associated to the lake, one uvala, nine gullies with a maxima length of 323 m and a main stream that measures 1421 m, together with the presence of colluvial, alluvial and doline deposits (Figure 1).…”
Section: Study Areamentioning
confidence: 99%
“…La zona se caracteriza por un predominio de suelos agrícolas (cereal de invierno y cultivos de secano), mientras que los pastos destinados al uso ganadero (porcino y ovino) están cubiertos por matorrales mixtos muy degradados compuestos por boj (Buxux sempervirens), enebro (Juniperus oxycedrus) y romero (Rosmarinus officinalis). Los suelos forestales están cubiertos por bosques mediterráneos en los que predominan encinas, coscojas, enebros (Juniperus oxycedrus) y quejigales (López-Vicente et al, 2009). …”
Section: Materials Y Métodosunclassified
“…Evaporite karst features mainly correspond to lake basins developed in collapse structures related to dissolution of subjacent Triassic and Eocene formations (Estaña, Montcortés, Bañolas; e.g. Canals et al, 2006;López-Vicente et al, 2009). Moreover, numerous dam projects have been severely affected by karst-related water leakage problems (Belsué, Canelles, Camarasa;Milanovic, 2000).…”
Section: General Overview Of the Spanish Geomorphologymentioning
confidence: 99%